Efficacy and safety of infliximab therapy in refractory upper respiratory tract sarcoidosis: experience from the STAT registry - Barba, Thomas; Marquet, Alicia; Bouvry, Diane; Cohen-Aubart, Fleur; Ruivard, Marc; Debarbieux, Sébastien; Khouatra, Chahéra; Vighetto, Alain; de Parisot, Audrey; Valeyre, Dominique; Sève, Pascal (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: Upper respiratory tract (URT) involvement in sarcoidosis may be refractory to corticosteroids and immunosuppressants. Whether TNF-antagonists are efficient and safe in such phenotype is unknown. Methods: STAT is a French national drug registry including patients presenting sarcoidosis treated with TNF alpha antagonists. All cases of biopsy-proven sinonasal and laryngeal sarcoidosis were extracted and retrospectively analyzed from July 2014 to July 2015. Results: Twelve patients presenting biopsy-proven sarcoidosis with URT involvement were included in the STAT registry. Infliximab appeared effective in decreasing URT symptoms, as assessed by a significant decrease of the e-POST (extra-pulmonary Physician Organ Severity Tool) (1.5 [0-2] vs 5 [1.5-5], p=0.03) and a corticosteroids-sparing effect (7.5mg per day [5-10] vs 17.5 mg per day [7.5-20], p=0.04) at the end of follow-up. Conclusions: TNF-antagonists may be an efficient treatment of refractory URT manifestations and should be discussed when prolonged or high dosages of corticosteroids despite immunosuppressive therapy are required.